2015
DOI: 10.1002/bdd.1989
|View full text |Cite
|
Sign up to set email alerts
|

Species‐ and gender‐dependent differences in the glucuronidation of a flavonoid glucoside and its aglycone determined using expressed UGT enzymes and microsomes

Abstract: Flavonoids occur naturally as glucosides and aglycones. Their common phenolic hydroxyl groups may trigger extensive UDP-glucuronosyltransferase (UGT)- catalysed metabolism. Unlike aglycones, glucosides contain glucose moieties. However, the influence of these glucose moieties on glucuronidation of glucosides and aglycones remains unclear. In this study, the flavonoid glucoside tilianin and its aglycone acacetin were used as model compounds. The glucuronidation characteristics and enzyme kinetics of tilianin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The glucuronidation characteristics of the flavonoid glucoside tilianin and its aglycone acacetin (flavones) were characterized with the use of human UGT isoforms, liver microsomes, and intestinal microsomes that were obtained from different animal species. Overall, and consistent with Kawase et al (61), higher glucuronidation rates attributed to higher UGT1A1 activities were evident in females across several species (62). The impact of aging on the glucuronidation of quercetin and genistein in male rat hepatic microsomes was also studied (63).…”
Section: Etiology Of the Heterogeneity In Flavonoid Admesupporting
confidence: 88%
“…The glucuronidation characteristics of the flavonoid glucoside tilianin and its aglycone acacetin (flavones) were characterized with the use of human UGT isoforms, liver microsomes, and intestinal microsomes that were obtained from different animal species. Overall, and consistent with Kawase et al (61), higher glucuronidation rates attributed to higher UGT1A1 activities were evident in females across several species (62). The impact of aging on the glucuronidation of quercetin and genistein in male rat hepatic microsomes was also studied (63).…”
Section: Etiology Of the Heterogeneity In Flavonoid Admesupporting
confidence: 88%
“…Furthermore, data from our lab also showed that higher resveratrol concentrations inhibit the formation of resveratrol-3-O-sulfate, which might also be observed in mice [ 24 ]. We decided to use male and not female mice in all experiments as recent papers [ 25 , 26 ] described significant gender-dependent differences in the glucuronidation of drugs and flavonoids in mice, with a higher formation rate of glucuonides in females than in males, which might be also true for resveratrol. In humans, such pronounced gender-difference in glucuronidation has not been observed so far.…”
Section: Discussionmentioning
confidence: 99%
“…In HLMs, the CL int value of diosmetin through 3′-OH was much higher than that of the 7-OH, and the CL int value of chrysoeriol through 4′-OH was about 32 times than that of the 7-OH pathway. For another, the K m values of diosmetin and chrysoeriol glucuronides were lower than a series of 7-OH, 3’-OH or 4’-OH flavonoids, such as acacetin glucuronide (K m was 14.465 μM)[34] and genistein glucuronides (K m was 15.1 μM)[35] (Table 1). …”
Section: Discussionmentioning
confidence: 99%